Tinjauan Filosofis Pendidikan Islam (Analisis Konsep Islam Mengenai Faktor Pendidikan): (Analisis Konsep Islam Mengenai Faktor Pendidikan) - Rinnanik, Rinnanik (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2017)
This study discusses a review of the philosophical concept of Islamic education by analyzing the Islamic concept of educational factors as an effort to educate the Islamic education. Islam is very concerned with education because with the right education and quality, civilized individuals will be formed that eventually led to the social moral life in this age of accelerating globalization dynamics. This is where the educational challenges including Islamic education that is expected to show itself in educating and produce learners who are highly competitive (qualified). Education is an integral factor that must be considered for the success of an education. For it should in the education process of these factors need to be a discussion as well as the special attention which later educational goals that have been designed that can be implemented perfectly good personal realization that belandaskan on the fundamentals of religion, al quran and hadith the prophet. Factors Islamic Education, among others: the Islamic concept of education, children (students), environmental and educational tool according to the teachings of Islam.